Pengaruh Tingkat Kebugaran Jasmani Terhadap Peningkatan Prestasi Siswa Sekolah Sepak Bola Bima Amora - Wibowo, Danatullah Loudry; Muhyi, Muhammad; Kusuma, Angga Indra; Utomo, Gatot Margisal (Program Studi Pendidikan Jasmani Kesehatan dan Rekreasi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Islam 45, 2025)
This study focuses on improving the physical fitness of elementary students, particularly those in grades 3-6 at SSB Bima Amora, as fitness is crucial for soccer performance. Better physical fitness can enhance achievements in soccer competitions. The study aims to benefit SSB Bima Amora Gresik students by promoting physical conditioning. A quantitative experimental method was used, involving 30 students aged 9-11 years, divided into 15 for the experimental group and 15 for the control group. Data collection was conducted through pretest and posttest assessments. The analysis in Chapter IV showed a p-value of 0.000, which is smaller than 0.05, leading to the rejection of H0 and acceptance of H1. The significance test (2-tailed) confirmed a positive impact on students' physical fitness, contributing to better soccer performance among 9-11-year-old students in Menganti, Gresik.